Impact of COVID-19 on Guillain Barre Syndrome (GBS) insights from an Iranian referral center - Mohammadali Arami; Rezafarhad Manteghifasaei; Mohammad Karimi; Puya Zandi; Mobina Javadi (Frontiers in Neurology)
BackgroundThe COVID-19 pandemic has raised concerns about various neurological complications, including Guillain-Barré syndrome (GBS). Understanding the characteristics and incidence of GBS during this period is crucial for clinical management and public health response.ObjectiveThis study aims to analyze the characteristics of GBS cases reported at an Iranian referral center during the COVID-19 pandemic and assess the relationship between GBS, COVID-19 infection, and vaccination.MethodsWe conducted a retrospective analysis of GBS cases referred to our center between 2018 and 2023. Clinical data, including demographic information, neurophysiological subtypes, COVID-19 and vaccination associated cases and outcomes were collected and analyzed. The frequency of GBS admission during pandemic compared with previous years. Characteristics of COVID-19 associated GBS and those vaccinated for COVID-19 was compared.ResultsA total of 334 patients were included to study. Our analysis revealed a notable increase in GBS cases during the pandemic. The incidence of vaccine-related GBS was significantly lower than that of GBS related to COVID-19 infection. Additionally, GBS patients diagnosed with COVID-19 presented more severe symptoms compared to those who developed GBS after vaccination.ConclusionAlthough the incidence of GBS increased during the COVID-19 pandemic at our center, it remains a rare complication of both COVID-19 and its vaccination. These findings highlight the need for ongoing surveillance of neurological complications during infectious disease outbreaks and vaccination campaigns.